The paradigm of intracellular parasite survival and drug resistance in leishmanial parasite through genome plasticity and epigenetics: Perception and future perspective - Kamran, Mohd.; Bhattacharjee, Rahul; Das, Sonali; Mukherjee, Sohitri; Ali, Nahid (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmania is an intracellular, zoonotic, kinetoplastid eukaryote with more than 1.2 million cases all over the world. The leishmanial chromosomes are divided into polymorphic chromosomal ends, conserved central domains, and antigen-encoding genes found in telomere-proximal regions. The genome flexibility of chromosomal ends of the leishmanial parasite is known to cause drug resistance and intracellular survival through the evasion of host defense mechanisms. Therefore, in this review, we discuss the plasticity of Leishmania genome organization which is the primary cause of drug resistance and parasite survival. Moreover, we have not only elucidated the causes of such genome plasticity which includes aneuploidy, epigenetic factors, copy number variation (CNV), and post-translation modification (PTM) but also highlighted their impact on drug resistance and parasite survival.